Bradykinin-evoked changes in cytosolic calcium and membrane currents in cultured bovine pulmonary artery endothelial cells. - Cannell, M B (1989)
1. Cultured bovine pulmonary artery endothelial cells were voltage clamped using a single microelectrode while cytosolic free calcium concentration ([Ca2+]i) was simultaneously measured using the fluorescent calcium indicator, Indo-1. 2. The resting current-voltage relationship was non-linear and exhibited marked inward rectification near the resting potential. In about 60% of cells examined, superfusion of saline resulted in a hyperpolarization and decrease in inward current. This result did not depend on the presence of agonist and is consistent with the presence of extracellular potassium accumulation in restricted spaces around the cell and the known dependence of the inward rectifier. In other cells there was no effect. 3. Resting [Ca2+]i was sensitive to membrane potential, decreasing continuously with membrane depolarization over the range -70 to +60 mV. This result is consistent with a simple pump-leak model and suggests that voltage-dependent calcium channels are not present in these cells. 4. Bradykinin (10 microM) increased [Ca2+]i after a delay of approximately 3 s. [Ca2+]i reached a peak after a further 3 s and declined over several minutes. 5. During the rise in [Ca2+]i evoked by application of bradykinin, there were no changes in the current-voltage relationship of the cell. These results question the role of a receptor-operated non-selective cation channel in mediating the increase in [Ca2+]i. This observation, coupled with the observed delay in the agonist-evoked response suggests that a second messenger system is involved in mediating the increase in [Ca2+]i. 6. Changes in the current-voltage relation started to occur about 30 s after the application of agonist. These changes could be explained by the activation of large-conductance potassium and non-selective cation channels with a reversal potential near 0 mV. The latter channels may mediate the plateau phase of the agonist-evoked response. 7. The results are discussed with respect to the pathways for calcium entry into the cell and possible explanations for discrepancies between the results of this and other studies are presented.